Domestic violence and related factors among ever married females in a rural area of southern India - Chauhan, Pooja; Shridevi, Kotina; Katkuri, Sushma (International Journal Of Community Medicine And Public Health, 2018)
Background: The WHO reports that the proportion of women who had ever experienced physical or sexual violence or both by an intimate partner ranged from 15% to 71%. According to NFHS-3 and India’s NCRB, the increasing cases of any form of violence against women and also the variation in its prevalence among different sections of the society indicate that it is preventable. This has been the motivation for conducting this study. The aim of the study was to know the prevalence, different forms and associated factors of domestic violence against ever married females between 15-49 years age. Methods: Community based cross-sectional study population included ever married females from 15 to 49 years. Sample size was calculated using openEpi online program. Simple random sampling was used. A pre-designed semi-structured questionnaire was used to collect data. Data was analyzed using SPSS software v24. Chi-square test was used. Results: It was observed that 33.5% (n=83) suffered from any form of violence and 29.4% (n=73) experienced physical violence at least once. Emotional abuse was seen in 12.5% whereas sexual abuse was seen in 4.4%. The experience of domestic violence by women was significantly related to the consumption of alcohol by the husband, education status of the females and their husband. Conclusions: By improving the literacy, and sensitizing about equal rights and need to look their wife as a life partner rather than a slave, an attempt can be made to break the chain of domestic violence.